Posició i funció dels connectors «a més (a més)», «però» i «doncs» en català escrit i oral - Bladas, Òscar (Caplletra. Revista Internacional de Filologia, 2008)
This article is an approach to the study of the syntactic positions that parentetic connectors take in oral discourse in Catalan –in sentential segments particularly– based on the analysis of three connectors with different meanings: «a més a més» (additive), «però» (contrastive) and «doncs» (consecutive). The methodology used is contrastive: firstly, the positions in which all three linking words stand in a corpus of written language (written press) are studied, and secondly, the results obtained arecompared with datum coming from an oral corpus constituted mainly of monologic texts. The comparison brings to light that conditions of production of oral modality (immediateness, lack of planning, etc) force to resorting to own strategies to guaranteethe connection of the text, like reinforcing a conjunction with a parentetic connector («a més a més»), to promote the conjunctive use of a connector («però») and to assure the connection among subject-rheme («doncs»)